The Influence of MSME Sustainability on Financial Performance with Network as a Moderating Variable (Case Study of MSMEs in Makassar City) - Siti Nurhana; Linda Arisanty Razak; Ramly (IECON: International Economics and Business Conference, 2024)
This study examines the impact of sustainability on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Makassar City, with business networking as a moderating variable. The independent variables are sustainability practices and business networking, while the dependent variable is financial performance. Challenges in this research include limited data on sustainability and networking, difficulties in measurement, varying levels of implementation, and the lack of proper reporting systems among MSMEs. Using a quantitative approach and survey method, data was collected from 50 MSMEs. Multiple regression analysis evaluated the direct impact of sustainability on financial performance, while moderation analysis assessed the role of business networking. The findings, processed using SPSS, reveal that both sustainability practices and networking positively affect MSMEs’ financial performance. The acceptance of the first hypothesis (H1) indicates that higher sustainability practices enhance financial performance. The second hypothesis (H2) confirms that strong networking further improves financial outcomes. Moreover, the third hypothesis (H3) highlights that networking moderates the relationship between sustainability and financial performance, demonstrating that a robust network amplifies the benefits of sustainable practices. This study underscores the importance of sustainability and networking in driving MSME financial success.